The Influence Of Organizational Culture, Work Discipline And Work Stress On Employee Performance At PT. Ciomas Adisatwa City Bengkulu - Gillang Prasetya; Taufik Bustami (Jurnal Akuntansi, Manajemen, Ekonomi Islam, 2024)
This research aims to determine the influence of organizational culture, work discipline and work stress on employee performance at PT. Ciomas Adisatwa, Bengkulu City. This type of research is a quantitative descriptive research type, the object of this research is the employees of PT. Ciomas Adisatwa, Bengkulu City, which is precisely located on Jl. Lake, Kel. Big Hamlet, District. Gading Cempaka, Bengkulu City, Bengkulu. The sampling method uses the Total Sampling technique, namely Total sampling. The number of respondents in this study was 40 people. The data collection method uses a questionnaire. The data analysis technique uses the Multiple Linear Regression Analysis Test, and Hypothesis Testing, namely the t test and f test.The results of this research can be concluded that the Organizational Culture variable has a positive and significant effect on Employee Performance, Work Discipline has a positive and significant effect on Employee Performance, Job Stress has a negative and significant effect on Employee Performance, and Organizational Culture, Work Discipline and Work Stress together has a significant effect on employee performance at PT. Ciomas Adisatwa, Bengkulu City.